Understanding the Social License to Operate from a Cultural Perspective: The Case Studies of Australia, Greece, and India - Rodolaki, Chrysanthi; Barakos, George (MDPI, 2023)
A reliable, sustainable, and transparent supply of critical raw materials is vital for developing future technologies and transitioning to a carbon emission-free world. However, mining can generate social, economic, and environmental impacts, compromising the sector’s public perception and jeopardising the social acceptance of operations. In various contexts, the social impacts of mining are assessed with different sets of indexes and targets. This study investigates cultural indicators of societal acceptance for mining critical raw materials in Australia, Greece, and India. Identifying and comparing the perception of mining in the three countries points out the difference in each society’s behaviour based on their culture.